Microwave-Assisted Synthesis of Chitosan/Polyvinyl Alcohol Silver Nanoparticles Gel for Wound Dressing Applications - Nguyen Thi Hiep; Huynh Chan Khon; Vo Van Thanh Niem; Vo Van Toi; Tran Ngoc Quyen; Nguyen Dai Hai; Mai Ngoc Tuan Anh (International Journal of Polymer Science)
The purpose of this study was to fabricate chitosan/poly(vinyl alcohol)/Ag nanoparticles (CPA) gels with microwave-assistance for skin applications. Microwave irradiation was employed to reduce silver ions to silver nanoparticles and to crosslink chitosan (CS) with polyvinyl alcohol (PVA). The presence of silver nanoparticles in CPA gels matrix was examined using UV-Vis spectroscopy, transmission electron microscopy, and X-ray diffraction. The interaction of CS and PVA was analysed by Fourier transform infrared spectroscopy. The release of silver ions was determined by atomic absorption spectrometry. The antimicrobial properties of CPA gels against P. aeruginosa and S. aureus were investigated using agar diffusion method. Finally, the biocompatibility and wound-healing ability of the gels were studied using fibroblast cells (in vitro) and mice models (in vivo). In conclusion, the results showed that CPA gels were successfully fabricated using microwave irradiation method. These gels can be applied to heal an open wound thanks to their antibacterial activity and biocompatibility.